Juhud al-Jahidz fi Bahtsi al-Ittishal al-Lafdzi - Muflihah, Muflihah; Bashori, M. (Institut Agama Islam Negeri Curup, 2022)
This study aims to examine the concept of communication according to al-Jahidz. Communication comes from Latin communication, which is rooted in the word communism, which means the same meaning of something. In other words, a communication event will take place if the people involved in it have the same perception or meaning of what is being communicated. As a term, communication can be defined as the delivery and reception of messages or information between two or more people using verbal (language) and nonverbal symbols. This article uses a descriptive qualitative method, which describes and analyzes in-depth verbal communication according to Al-Jahidz. The data collection technique makes use of primary data sources through documents of al-Jahidz books (al-Bayan wa al-Tabyin, al-Hayawan, al-Risalah Li al-Jahidz, al-Hayawan) and other books that discuss al-Jahidz (Usmaniyah Li al-Jahidz, al-Bukhala’ Li al-Jahidz, al-Malamich al-Adaiyah Li al-Jahidz). The results reveal that Al-Jahidz is an Arabic linguist who discusses the theory of verbal communication which includes: the concept of verbal communication, forms of verbal communication and its characteristics, the effect of verbal communication on the same speaker alongside its relationship to the intellectual level, the influence of physical signs or movements on strengthening and controlling verbal performance, commissions, and their effects on verbal performance, varying performance effects on verbal communication, and preference for speaking over silence.